A mathematical model of DIAJET abrasive water jet cutting - Claffey, E. (Cranfield University, 1996)
A mathematical model of ductile material cutting with an abrasive suspension jet has been developed. This is based on erosive wear of material by solid particle impact. The largest contribution is assumed to be from near-normal impacts. This 'deformation wear' causes work-hardening and subsequent brittle fracture of the material. A threshold velocity exists, below which no erosion takes place. The value of this velocity is dependent on the material ultimate tensile strength. The depth of cut achievable for a given traverse speed is dependent on the threshold velocity and the fracture strength of the material. For brittle fracture this has a value of E/10. A simulation of particle acceleration within a cutting nozzle was also undertaken by applying the Navier-Stokes equation to the boundary conditions. This revealed that the particle velocity is almost identical to the theoretical (Bernoulli's) slurry velocity for the nozzles used in this project. The model has been validated against a range of operating parameters such as pressure, abrasive, abrasive concentration, and material properties. This has confirmed the validity of the assumptions, with a good correlation. Some predictions, however, gave a better fit if only 60% of the measured abrasive discharge was used. Highly alloyed materials produced a less satisfactory fit to the model.